Analysis of the influence of roll size change on electromagnetic heat conversion capacity and roll profile control characteristics in the RPECT. (15th June 2022) - Liu, Wenwen; Li, Ting; Wang, Tao; Fu, Xiaobin; Du, Fengshan
Highlights: The effect of roll diameter variation on electromagnetic heat conversion capacity is analyzed. The roll profile control characteristics and practical application effect of RPECT are analyzed. The effect of roll surface cooling on RPECT is discussed. The design principle of roll size in RPECT is given. Abstract: RPECT is proposed to solve the problem of flatness control for cold-rolled strip processing. As one of the core components of this technology, the roll size is the key factor that affects the capability of the heat conversion and the roll profile control. So an electromagnetic thermal mechanical coupled axisymmetric model under the same electromagnetic rod structure and size is established to research this problem. After research, the results show that, with the roll diameter increasing, the induction heating efficiency changes a little, the average contact-stress increases, the roll crown decreases. Moreover, the control ability of roll surface cooling on roll temperature, roll crown and roll profile decreases. And the control effect on roll temperature, roll crown and roll profile weakens with the increase of roll surface cooling intensity. Therefore, when the electromagnetic rod structure is determined, the principle to be followed in the design of the roll used in the RPECT should be as follows: on the premise of meeting the strength and stiffness requirements of roll, the roller diameter should be small as much as possible.